2015
DOI: 10.3233/jad-150307
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Delivery of Intranasal Insulin: Mechanisms of Uptake and Effects on Cognition

Abstract: Intranasal insulin has shown effficacy in patients with Alzheimer’s disease (AD), but there are no preclinical studies determining whether or how it reaches the brain. Here, we showed that insulin applied at the level of the cribriform plate via the nasal route quickly distributed throughout the brain and reversed learning and memory defficits in an AD mouse model. Intranasal insulin entered the blood stream poorly and had no peripheral metabolic effects. Uptake into the brain from the cribriform plate was sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 44 publications
2
83
0
1
Order By: Relevance
“…The level of radioactivity in each of the regions and the serum was measured in a Wizard2 Automatic Gamma Counter (PerkinElmer, Waltham, MA, USA). The percentage of injected dose present in a milliliter of serum (%Inj/mL) and the percentage of the injected dose taken up per gram of tissue (%Inj/g) was calculated as previously described [55,56]. …”
Section: Methodsmentioning
confidence: 99%
“…The level of radioactivity in each of the regions and the serum was measured in a Wizard2 Automatic Gamma Counter (PerkinElmer, Waltham, MA, USA). The percentage of injected dose present in a milliliter of serum (%Inj/mL) and the percentage of the injected dose taken up per gram of tissue (%Inj/g) was calculated as previously described [55,56]. …”
Section: Methodsmentioning
confidence: 99%
“…Intranasal insulin therapy has been shown to improve memory function in AD patients and in healthy individuals (Benedict et al , 2004; Reger et al , 2006; Hanson & Frey, 2008; Reger et al , 2008; Craft et al , 2012; Schioth et al , 2012b; Freiherr et al , 2013; Craft et al , 2017). Further, animal models of aging and AD also show the positive impact of intranasal insulin in combating cognitive decline (Francis et al , 2008; Marks et al , 2009; Apostolatos et al , 2012; de la Monte, 2013; Adzovic et al , 2015; Salameh et al , 2015; Anderson et al , 2016; Maimaiti et al , 2016). Despite these promising outcomes, the mechanisms of action in the brain, and specifically on neurons of the hippocampus where insulin plays a recognizable role in learning and memory (Zhao et al , 1999; Zhao et al , 2004), remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Several small‐scale clinical trials have shown that intranasal insulin improves memory and attention in healthy participants, as well as in patients with mild cognitive impairment and AD (Craft et al ., 2012). Preclinical studies have also been conducted to confirm the cognitive improvement by intranasal insulin and the way how it reaches the brain (Marks et al ., 2009; Salameh et al ., 2015). However, the mechanisms underlying improved memory with insulin treatment remain unclear.…”
Section: Introductionmentioning
confidence: 99%